The development of non-coding RNA ontology. (2016) - Huang, Jingshan; Eilbeck, Karen; Smith, Barry; Blake, Judith A.; Dou, Dejing; Huang, Weili; Natale, Darren A.; Ruttenberg, Alan; Huan, Jun; Zimmermann, Michael T.; Jiang, Guoqian; Lin, Yu; et al.
Identification of non-coding RNAs (ncRNAs) has been significantly improved over the past decade. On the other hand, semantic annotation of ncRNA data is facing critical challenges due to the lack of a comprehensive ontology to serve as common data elements and data exchange standards in the field. We developed the Non-Coding RNA Ontology (NCRO) to handle this situation. By providing a formally defined ncRNA controlled vocabulary, the NCRO aims to fill a specific and highly needed niche in semantic annotation of large amounts of ncRNA biological and clinical data.